Depresión y funcionalidad familiar en adolescentes de la Institución Educativa Rosa Agustina Donayre de Morey Iquitos 2023 - Oliveira Piñeiro, Marininha Solange (2024)
The goal was to determine the relation between depression and family functionality in adolescents of the Educational Institute, Rosa Agustina Donayre de Morey, Iquitos 2023. The study was quantitative with a non experimental, descriptive, correlational design. The student population consisted of 254 students from 14 to 17 years old from such educational institution. The Zung test and the family (APGAR) tools were applied. The results obtained regarding gender: 142 (55.9%) belong to the male sex, while 112 (44.1%) belong to the female sex, 123 (48.4%) showed minor depression, while 12 (4.7%) reported no depression, 82 (32.3%) showed minor family dysfunction, while 36 (14.2%) showed good family functionality. Acording to the level depression and family functionality, 53 (20.9%) reported depression and mild family dysfunction, while 0 (0.0%) reported the absence of depression and severe family dysfunction, 1 (0.4%) presented severe depression and good family functionality. The statistical test of X with continuity correction was applied, obtaining X² tests with continuity correction 53.3 gl 9 p< 001 < α < 0.05, which is significant, approving the proposed research hypothesis: There is a statistically significant relation between depression and family functionality in students of the IE RADM, Iquitos year 2023.